2021
DOI: 10.1002/mmce.22795
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid metasurface loaded tri‐port compact antenna with gain enhancement and pattern diversity

Abstract: A tri‐port compact antenna loaded on hybrid metasurface (MS) with gain enhancement and pattern diversity is proposed in this article. The antenna consists of three analytically designed contorted radiators (Ant‐1, Ant‐2, and Ant‐3). A koch‐fed fractal aperture ground plane is used to improve impedance matching and port isolation, thus eliminating supplementary decoupling networks. Ant‐1 is 45° tilted, operating in wideband mode. Ant‐2 is one‐fourth, Ant‐3 is one‐half in electrical lengths with L‐shaped metalli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…The proposed antenna has a peak gain variation from 7.5 to 8.5 dBi. It is also observed that, MTS layer has a better performance compared to earlier reported antennas in [537, 39, 40], and witness better reflection properties due to the presence of coupling effects [41] of inductance and capacitance, which control the fringing fields to be effectively coupled out with the radiated fields. Here, the radiation pattern at different frequencies is measured in the anechoic chamber and their plots are presented in Figs 5(a) and (b).…”
Section: Resultsmentioning
confidence: 88%
“…The proposed antenna has a peak gain variation from 7.5 to 8.5 dBi. It is also observed that, MTS layer has a better performance compared to earlier reported antennas in [537, 39, 40], and witness better reflection properties due to the presence of coupling effects [41] of inductance and capacitance, which control the fringing fields to be effectively coupled out with the radiated fields. Here, the radiation pattern at different frequencies is measured in the anechoic chamber and their plots are presented in Figs 5(a) and (b).…”
Section: Resultsmentioning
confidence: 88%
“…48 Due to highdemand of UHF RFID applications toward automation, tracking, identification, security, logistics management, and so on, the antenna performance metrics like À10 dB impedance bandwidth (IBW), 3-dB axial ratio bandwidth (ARBW), and CP gain need to be enhanced for scalability. To understand insights about importance of CP, aimed to minimize polarization mismatch in between readers and tags; evaluation of characteristics mode analysis (CMA) [49][50][51][52][53][54][55] is performed, that help in predicting modal significance (MS), modal current, modal pattern, characteristics angle (φ n ), and eigen value (EV) for different antenna models. Comparison of performance analysis with the CP antennas [56][57][58][59][60][61][62][63][64][65][66][67][68][69] are reported in Tables 1 and 2.…”
Section: Introductionmentioning
confidence: 99%
“…As a result of which, it improves antenna coupling process and the radiation strength at the boresight direction is also improved, significant for UHF RFID applications. Here, characteristics mode theory (CMT) using CST microwave studio suite (CST-MWS) is implemented to study effective coupling modes, modal radiation patterns, [50][51][52][53][54] and interpret the insights behind the existence of CP behavior. 55 The analysis shows asymptotic nature at the CP band and symptotic above and beyond it.…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, compactness and low-profile in MIMO configuration can leverage spatial diversity, which can be achieved by localization and orientation of conducting elements to broadcast radiation diversity. 4 Secondly, isolating conducting elements increases signal throughput and reduces near-field mutual coupling. Thirdly, low Envelope channel coefficient (ECC) and diversity metrics to assert T X and R X of multiple data streams to improve wireless throughput.…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, compactness and low‐profile in MIMO configuration can leverage spatial diversity, which can be achieved by localization and orientation of conducting elements to broadcast radiation diversity 4 . Secondly, isolating conducting elements increases signal throughput and reduces near‐field mutual coupling.…”
Section: Introductionmentioning
confidence: 99%